DEMOGRAPHIC PATTERN OF MALE BREAST CANCER: AN INSTITUTIONAL BASED STUDY - Tasneem, Shahida; Khan, Mah Muneer; Khawaja, Mohammad Younas (Journal of Ayub Medical College Abbottabad, 2011)
Background: Male breast cancer incidence rises with age with peak in the 6th & 7th decade. It is one of the rare diseases and accounts for less than 1% of all malignancies worldwide. It is usually diagnosed in the late stage with poor prognosis. Objective: The purpose of this study was to know the demographic pattern and tumour characteristic of breast cancer in men reported at Institute of Radiotherapy and Nuclear Medicine (IRNUM), Peshawar. Methods: Retrospective data was collected from the (IRNUM), Peshawar for a period of three years (2006ˆ’2008). The evaluation was done from the histopathological reports of mastectomy and biopsy specimens. All male patients in the age group 26ˆ’86 year with breast cancer were included in the study. The age of the patients and tumour characteristics recorded were size, grade, type, skin involvement and stage. Results: Total number of male patients with breast cancer were 31 (2.1%) out of the total patients with breast malignancy during the study period with the mean age of 58.3 years. Tumour size ranged from 2 to 12 Cm. with average of 3.6 Cm. Invasive ductal carcinoma was found in 87%, papillary carcinoma in 6.5%, each of malignant fibrous histocytoma and sarcoma in 3.2% cases. Maximum number of patients was of grade II (41%).Patients in whom stage of the disease was known were 22 cases with 45.5% had stage III disease and 32% had stage IV disease. Skin involvement was found positive in 8 (25.8%). Conclusion: Due to poor health care system breast cancer is diagnosed in a late stage of the disease and prognosis is poor. Keywords: Male, breast malignancy, Stage, grade, type